TaCertoIssoAI: A Data Lake for Misinformation Analytics from WhatsApp in Brazil - Lira, Cauê Paiva; Costa, Luiz Felipe Diniz; Silva, Pedro Henrique Ferreira (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
This paper presents the analytics data lake of TaCertoIssoAI, a WhatsApp-based fact-checking platform operating in Brazil. Verified messages are anonymized and stored in a hybrid data architecture on Google Cloud, combining BigQuery for analytical workloads (OLAP) and Firestore for operational access (OLTP). The stored fact-checks follow a claim-oriented data model that supports multimodal content representations, together with vector embeddings for semantic search. A public analytics front-end allows users to filter, explore, and export fact-checking data. With over 7,200 users and 14,000 verified messages stored, the system provides a live dataset for analyzing misinformation patterns on messaging platforms and social media. The project has also won national technology competitions, been presented at a conference held at MIT, and received coverage from national news outlets such as G1.